KRIMINALISASI PERBUATAN CABUL YANG DILAKUKAN OLEH PASANGAN SESAMA JENIS KELAMIN (HOMOSEKSUAL) - Riswan Erfa (Arena Hukum)
Abstract The writing of Journal in the form of research is motivated by three issues. First, juridical problems that can be observed from the vacuum of norm. Article 292 of the Criminal Code only formulate criminal sanctions for perpetrators who commit indecent acts between same-sex with child victim. Second, theoretical issue, crime can be interpreted as a mala in se or bad deeds in itself, prohibitted behavior based on public agreement on procedures for the prohibition. Third, sociological problems that can be observed from the discovery of indecent acts performed by same-sex couples and the refusal of the major community to the existence of homosexuals. Aims in writing of this journal are formulated in two formulation. First: To analyze and explain indecent acts committed by same-sex couples should be categorized as a criminal act (offense) in Indonesia. Second: To analyze and explain concept of criminal law policy formula for indecent acts by criminalizing same-sex couples in Indonesia. The writing of Journal uses normative legal research methods. Acts committed by same-sex couples should be categorized as a criminal act, first: Juridical basis, can be based on Law Number 11 of 2012, the Pancasila as well as several articles in the Constitution of Indonesia and the last is Article 1 (1) of the Criminal Code concerning on the principle of legality. Second: the theoretical basis, can be based on the criminalization of indecent acts to the indecent acts undertaken by same-sex couples have met the general criteria of the criminalization supported by the form of criminalization theory, the theory of natural law, positivism, and human rights. Third: sociological basis, indecent acts by same-sex couple as an act that is not in line with the spirit of the nation, the public reaction to the rejection of homosexual activity, and not in line with the rules of indigenous peoples. Furthermore, the concept of policy formulation in the criminal law to criminalize the indecent acts performed by same-sex couples in Indonesia can be made by taking into account several things. Noting the criminal law policy and pay attention to the comparison of conceptual settings.